PENGARUH PENDAPATAN DAN HARGA PANGAN TERHADAP DIVERSIFIKASI PANGAN DI PULAU JAWA - Manuntun Parulian Hutagaol; Roeskani Sinaga (Sekolah Menengah Kejuruan (SMK) Pustek, 2022)
This study uses data from the National Socio-Economic Survey (Susenas) for the period March 2015, March 2016 and March 2017 which was collected by the Central Statistics Agency (BPS). This study uses the Berry Index (BI) and Modified Berry Index (MBI) analysis methods to measure the level of household food diversification. The results of the analysis state that rice is still an important food ingredient for the people of Java, but along with the increase in household income groups, the proportion of rice consumption also decreases and shifts to consumption of ready-to-eat food and beverages. The level of food diversification is already high. With the increase in per capita income, the level of food diversification also increases. Food diversification experienced positive growth from year to year. Thus, the high income group has the largest share of food expenditure in the processed food and beverage commodity group. In general, food diversification is influenced by food expenditure, food commodity prices, number of family members and area of ??residence. The increase in the price of rice, fish, eggs, vegetables, nuts and fruits reduces the level of diversification. This is because these commodities, especially rice, are staple commodities that are difficult to substitute. An increase in income levels will increase food diversification. Increasing the number of family members reduces the level of diversification. Households in urban areas have a higher level of diversification than households in rural areas.